Physicochemical aspects of the giant multinucleate cell formation - Smetana, K; Sulc, J; Krcová, Z (Experimental and molecular pathology, 1987)
Process of multinucleate cell formation was studied under two conditions: (1) during the perichondral ossification of the chick embryonal tibia, and (2) in foreign-body reaction against polyhydroxyethylmethacrylate (POLYHEMA) and copolymer of hydroxyethylmethacrylate and methacrylic acid (POLYHEMA-MA) subcutaneously implanted into the rat. Multinucleate cells covered a surface of the substrate with relatively low hydrophylia and with low or without acidic groups (mineralized bone and POLYHEMA). On the other hand, no (POLYHEMA-MA) or only exceptional (nonmineralized resorbed cartilage) multinucleate cells were visible on the substrate rich in water and acidic groups. This similarity is not surprising, since it is accepted that both cell types represent a specialized phagocytic element. These results demonstrate that precursor cells can fuse only under convenient conditions. Forces analogous to hydrophobic and electrostatic interactions probably participate in this process.
Keywords: Chick Embryo; Animals; Chemistry, Physical; Methacrylates; Polyhydroxyethyl Methacrylate; Female; Foreign-Body Reaction; Cartilage; Hydrogen-Ion Concentration; inbrední kmeny potkanů; methakryláty; Prostheses and Implants; polyhydroxyethylmethakrylát; ženské pohlaví; reakce na cizí těleso; Osteoclasts; Cell Nucleus; chemické jevy; fyzikální chemie; Rats, Inbred Strains; osteoklasty; extracelulární matrix; Chemical Phenomena; voda; buněčné jádro; Water; chrupavka; krysa rodu Rattus; Extracellular Matrix; protézy a implantáty; zvířata; koncentrace vodíkových iontů; Rats; kuřecí embryo